25-Hydroxyvitamin D level, vitamin D intake, and risk of stroke: A dose–response meta-analysis. Issue 7 (July 2020) - Shi, Han; Chen, Hanze; Zhang, Yun; Li, Jinwei; Fu, Kailei; Xue, Weishuang; Teng, Weiyu; Tian, Li
Summary: Background & aims: A growing number of studies have shown that vitamin D are related to the risk of stroke, however, the dose–response association between vitamin D and the risk of stroke is still unclear. Accordingly, we conducted a dose–response meta-analysis to evaluate the relationships between 25-hydroxyvitamin D [25(OH)D] level, vitamin D intake, and the risk of stroke by summarizing cohort studies. Methods: PubMed, Embase, Cochrane and the Web of Science database were searched for related studies. Cohort studies examining the influence of 25(OH)D level and vitamin D intake on stroke risk were summarized. Dose–response relationships were determined using a random-effect model. Results: Twenty cohort studies involving 217, 235 participants were included. The pooled relative risk for the high-versus-low categories was 0.74 (95% CI: 0.66–0.83) for 25(OH)D level, and 0.75 (95% CI: 0.57–0.98) for vitamin D intake. In addition, there were non-linear relationships between 25(OH)D level, vitamin D intake, and stroke risk. The incidence of stroke was reduced to its lowest point, with a reduction of about 20%, when 25(OH)D level was about 50 nmol/L or vitamin D intake was about 12 μg/day. Conclusion: 25(OH)D level and vitamin D intake were both inversely related to stroke risk, with a non-linear dose–response relationship.